Revision of the South American genus Parorphula (Orthoptera: Acrididae; Hyalopterygini) with the description of a new genus - Donato, Mariano Humberto (2004)
In this study Parorphula is re-described based on characters from the external morphology and genitalia. This genus comprised two species: p. pallidinota and P. latipennis, that were described based mostly on charcaters from external morphology. The morphological analysis conducted in this study plus the support of results from a cladistic analysisshowed that external morphological characters justify the creation of a new genus for P. latipennis. Therefore, the genus Neorphula is proposed and the new combination is established.